PENGARUH BEBAN KERJA, PELATIHAN, DAN KEPUASAN KERJA TERHADAP KINERJA GURU SDIT NURUL IMAN PONDOK BAMBU SELAMA PEMBELAJARAN DARING DI SITUASI PANDEMI COVID-19 - Mitha Aulia Valentino, (2021)
The purpose of this quantitative study to analyze the effect of Workload, Training, and Job Satisfaction on Teacher Performance at SDIT Nurul Iman Pondok Bambu during online learning in the COVID-19 pandemic situation. The sample used in this study were 50 teachers which obtained by saturated sampling technique. Data collection was carried out using primary data conducted by questionnaires. The data analysis technique used are descriptive, essential data, and simultaneous F test through Smart Partial Least Square (PLS) 3.0. The results of this study indicate that (1) Workload have a positive and significant effect on Teacher Performance at SDIT Nurul Iman Pondok Bambu (2) Training have a positive and significant effect on Teacher Performance at SDIT Nurul Iman Pondok Bambu (3) Job Satisfaction have a positive and significant effect on Teacher Performance at SDIT Nurul Iman Pondok Bambu. The F-test results which was conducted manually indicate that Workload, Training, and Job Satisfaction have simultaneous effect on Teacher Performance at SDIT Nurul Iman Pondok Bambu.